How do you factor the trinomial $10{x^2} + 11x - 6 = 0$?
Answer
Verified
444k+ views
Hint:A trinomial is a polynomial which has three terms which are connected by plus or minus symbols. Trinomials are often in the form ${x^2} + bx + c$ but it is not true for all the cases. Trinomials which are in the form of ${x^2} + bx + c$ can be factored as the product of two binomials. Here, in this question we can factor the given trinomial by grouping.
Complete step by step solution:
Given a trinomial, $10{x^2} + 11x - 6 = 0$.
In order to solve this given polynomial, we must first look for two numbers which meet the following characteristics:
1. Both the numbers must have a product same as the product of first and last coefficients $\left( {10 \times - 6 = - 60} \right)$.
2. Both the numbers must have a sum same as the middle term $\left( {11} \right)$.
Now, we have to examine all those factor pairs whose product is $ - 60$ and their sum is $11$. Some of the possible factor pairs are:
$ - 1$ and $60$, $1$ and $ - 60$
$ - 2$ and $30$, $2$ and $ - 30$
$ - 3$ and $20$, $3$ and $ - 20$
$ - 4$ and $15$, $4$ and $ - 15$
$ - 5$ and $12$, $5$ and $ - 12$
$ - 6$ and $10$, $6$ and $ - 10$
The only pair whose sum is equal to$11$ is $ - 4,15$.
Since, $15x - 4x = 11x$, so we replace $11x$ in the given trinomial by $15x - 4x$. After replacing we get,
$
\Rightarrow 10{x^2} + 11x - 6 = 0 \\
\Rightarrow 10{x^2} + 15x - 4x - 6 = 0 \\
$
Now, we can factor the obtained polynomial by grouping. We start grouping by sorting the trinomial into groups of two.
$ \Rightarrow \left( {10{x^2} + 15x} \right) - \left( {4x + 6} \right) = 0$
Factor the common term from both the groups.
$ \Rightarrow 5x\left( {2x + 3} \right) - 2\left( {2x + 3} \right) = 0$
Taking the term$\left( {2x + 3} \right)$common, we get,
$ \Rightarrow \left( {2x + 3} \right)\left( {5x - 2} \right) = 0$
Thus, this is trinomial completely factored. This solution can be used to find the values of $x$. The values of $x$ can be calculated by putting the terms $\left( {2x + 3} \right)$ and $\left( {5x - 2} \right)$ equal to zero.
$
\Rightarrow 2x + 3 = 0 \\
\Rightarrow x = - \dfrac{3}{2} \\
$ $
\Rightarrow 5x - 2 = 0 \\
\Rightarrow x = \dfrac{2}{5} \\
$
Hence, this is our required solution.
Note: Students should remember that since the product of the first and last term is negative, one number of the factor pair should be negative and moreover, this means that the sum of $11$ should be created by the difference of those factor pair’s numbers. To check if values of $x$ are correct or not, students can substitute the desired values of $x$ in the given polynomial and see if LHS=RHS, then their solution is correct.
Complete step by step solution:
Given a trinomial, $10{x^2} + 11x - 6 = 0$.
In order to solve this given polynomial, we must first look for two numbers which meet the following characteristics:
1. Both the numbers must have a product same as the product of first and last coefficients $\left( {10 \times - 6 = - 60} \right)$.
2. Both the numbers must have a sum same as the middle term $\left( {11} \right)$.
Now, we have to examine all those factor pairs whose product is $ - 60$ and their sum is $11$. Some of the possible factor pairs are:
$ - 1$ and $60$, $1$ and $ - 60$
$ - 2$ and $30$, $2$ and $ - 30$
$ - 3$ and $20$, $3$ and $ - 20$
$ - 4$ and $15$, $4$ and $ - 15$
$ - 5$ and $12$, $5$ and $ - 12$
$ - 6$ and $10$, $6$ and $ - 10$
The only pair whose sum is equal to$11$ is $ - 4,15$.
Since, $15x - 4x = 11x$, so we replace $11x$ in the given trinomial by $15x - 4x$. After replacing we get,
$
\Rightarrow 10{x^2} + 11x - 6 = 0 \\
\Rightarrow 10{x^2} + 15x - 4x - 6 = 0 \\
$
Now, we can factor the obtained polynomial by grouping. We start grouping by sorting the trinomial into groups of two.
$ \Rightarrow \left( {10{x^2} + 15x} \right) - \left( {4x + 6} \right) = 0$
Factor the common term from both the groups.
$ \Rightarrow 5x\left( {2x + 3} \right) - 2\left( {2x + 3} \right) = 0$
Taking the term$\left( {2x + 3} \right)$common, we get,
$ \Rightarrow \left( {2x + 3} \right)\left( {5x - 2} \right) = 0$
Thus, this is trinomial completely factored. This solution can be used to find the values of $x$. The values of $x$ can be calculated by putting the terms $\left( {2x + 3} \right)$ and $\left( {5x - 2} \right)$ equal to zero.
$
\Rightarrow 2x + 3 = 0 \\
\Rightarrow x = - \dfrac{3}{2} \\
$ $
\Rightarrow 5x - 2 = 0 \\
\Rightarrow x = \dfrac{2}{5} \\
$
Hence, this is our required solution.
Note: Students should remember that since the product of the first and last term is negative, one number of the factor pair should be negative and moreover, this means that the sum of $11$ should be created by the difference of those factor pair’s numbers. To check if values of $x$ are correct or not, students can substitute the desired values of $x$ in the given polynomial and see if LHS=RHS, then their solution is correct.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE